Pembuatan E-Logbook Kegiatan Harian Karyawan Honorer Di Dinas Perpustakaan Dan Kearsipan Kota Samarinda - Anton Febrianto; Badriyah Ani Kusuma Putri; Muhammad Rizki Maulana; Ramayasin Gymnastiar; Abdul Rahim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to explore the process of creating daily logbooks for contract employees at the Library and Archives Department of Samarinda City and to assess the practicality of these logbooks. The research findings indicate that the implementation of an E-logbook for the daily activities of contract employees in the aforementioned department can be considered a significant innovation in human resource management. This E-logbook facilitates the easy and efficient recording and tracking of daily employee activities. Furthermore, the E-logbook proves instrumental in managing the daily tasks of contract employees, enhancing accountability, and aiding in more informed decision-making within the company or organization.